Viewpoint: Weak versus Strong Sustainability - Robert U. Ayres; Jeroen C.J.M. van den Bergh; John M. Gowdy (Tinbergen Institute, 1998)
The meaning of sustainability is the subject of intense debate among environmental and resourceeconomists. Perhaps no other issue separates more the traditional economic view of the naturalworld from the views of most natural scientists. The debate currently focuses on the substitutabilitybetween the economy and the environment or between "natural capital" and "manufacturedcapital"– a debate captured in terms of "weak" vs. "strong" sustainability. In this paper the variousinterpretations of these concepts are examined. In addition, the goal of weak sustainability iscritically evaluated. Attention is devoted to, among other things, utility and lexicographicpreferences, economic valuation, natural science perspectives on sustainability, and the notion of"consilience" as recently suggested by E.O. Wilson.
Keywords: 330; Nachhaltige Entwicklung; Theorie